Prelude. - L'Engle, Madeleine. (Vanguard Press, 1968)
Sent to a Swiss school after the death of her mother, a young girl tries to cope with the problems of growing up and at the same time maintain her ambition to be a concert pianist.
Especially adapted for young people by the author from the first part of her novel, The small rain.
Sent to a Swiss school after the death of her mother, a young girl tries to cope with the problems of growing up and at the same time maintain her ambition to be a concert pianist.